Modelagem analítica da temperatura de corte no torneamento do ferro fundido vermicular utilizando insertos de metal duro revestidos experimentalmente pelo processo sol-gel - Bruna Aparecida Rezende (2020)
In order to obtain better cutting tools performance, the coatings can be an alternative to the machining process. The goal of the coating is to improve tribological conditions in the chiptool and tool-workpiece interfaces. Due to this, in this work, the behavior of uncoated, Al2O3 and multilayer (TiO2 and Al2O3) coated tungsten carbide (WC) inserts by the sol-gel process used in the turning process of compacted graphite iron was studied. Overall, the deposited coatings showed good adhesion to the substrate. The scratch test indicated that the multilayer coating showed better adhesion on the substrate. The pin-on-disc tests indicated that lower friction coefficients were found for the coated tools up to 100 m of the sliding distance. To verify the influence of the cutting parameters (vc and f) and the coating, a full factorial design (matrix 3²4¹) was made. The analysis of variance (ANOVA) was used to evaluate the influence of the cutting parameters and tool coating on the cutting force, roughness and chip temperature. The results demonstrated that the lower cutting forces were obtained using the multilayer coated tool. The increase of the cutting speed contributed to minimize the roughness parameters, different from the feed. For the chip temperature, lower values were obtained when the multilayer insert was used. The increase of cutting speed and feed contributed to a higher chip temperature. Finally, a numerical modeling was performed using the finite elements method (FEM). The numerical model was validated through the experimental results of the chip temperature. An analytical model for both chip and interface (chip/tool) temperature was obtained by the linearization technique. Thus, an improved Gottwein model was created using not only cutting speed, but also the parameters feed and equivalent thermal conductivity. Both improved Gottwein model and FEM showed similar results when compared to the experimental values obtained.